Pan-cancer analysis of the immunological and oncogenic roles of ATAD2 with verification in papillary thyroid carcinoma - Zhecheng Li; Yaxin Zhao; Peng Huang; Zhaoyi Wu; Dengjie Ouyang; Adolphus Osei Nyarko; Lei Ai; Zhejia Zhang; Shi Chang (Scientific Reports)
Abstract ATAD2 (ATPase Family AAA Domain-Containing 2) is highly expressed across varies tumor types, yet its common roles in tumor progression and immune interaction remain unclear. We analyzed the expression and alteration profiles of ATAD2, along with its diagnostic and prognostic role in pan-cancer, utilizing TCGA, GTEx, CPTAC, HPA, and cBioPortal databases. Furthermore, we examined the relationship between ATAD2 and immune infiltration utilizing single-cell sequencing data and TCGA database. Additionally, the expression and oncogenic functions of ATAD2 were verified in papillary thyroid carcinoma (PTC) through MTT, wound-healing, transwell, and flow cytometry assays. Our results revealed significant overexpression of ATAD2 in most cancers, strongly associated with poor prognosis. Amplification was the most frequent alteration type of ATAD2, with its mutation correlating with improved overall survival. ATAD2 was positively correlated with multiple inhibitory immune checkpoints and closely associated with the immunosuppressive microenvironment, particularly in PTC. In vitro experiments demonstrated that ATAD2 promoted the proliferation, migration, and invasion of PTC cells by activating the PI3K-AKT pathway and modulating the G1/S cell cycle checkpoint. Collectively, ATAD2 holds promise as a biomarker for pan-cancer diagnosis and prognosis, as well as a predictor of immunotherapeutic responsiveness and a therapeutic target to enhance the efficacy of existing anti-tumor immune therapies.